Researching contexts, practices and pedagogies in English for academic purposes - Blaj-Ward, Lia; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book is a point of reference for EAP professionals planning to conduct or commission research into learning, teaching, professional development or quality assurance in EAP. It draws on academic and professional debates to inspire further research and practical initiatives to enhance EAP provision.
Keywords: Education; Linguistics; Applied linguistics; English language; Language and education; Language and languages -- Study and teaching; Education; Language Education; Applied Linguistics; Linguistics, general; Language Teaching; English